Inventarisasi Jamur Pelapuk Kayu dari Hutan Lereng Selatan Gunung Merbabu Jawa Tengah - Arya, Aris Munandar, Triastuti Rahayu, S.Si, M.Si (2017)
Merbabu mountain is located in the region of Central Java province and including a mountain volcano that no longer active. Geographically the mountain is located 7,5 South Latitude and 110,4 East Longitude with a height of 1000 m asl up to 3142 m sal height, mostly mountainous topography are hilly and there are ravines and steep cliffs. Wood-rot fungus are fungus are often found growing on rotten wood trunk or base of the tree is still alive. The purpose of this research is knowing the diversity of wood rot fungi in the south slopes forest of Mount Merbabu in Central Java. This study uses non-experimental studies (exploration) from the South Slope Forest of Merbabu Mountain, Selo Boyolali, Cental Java on February, 2nd 2017. The sampling was conducted along a hiking trail through Selo Merbabu of elevation 1800 m.asl (basecamp) until 2000 m.asl. Large area 40x500 m2 sampling area and sampling is done at every meeting and not do it again if it is found the same type of fungus with the previous encounter. Wood-rot fungi identification was performed using identification keys of the book The Complete Encyclopedia of Mushrooms and The Great Encyclopedia of Mushrooms. The results showed that found 13 families and 23 species which dominates was from Polyporaceae Family, with 9 species founded.